Comb-shaped polyurethane coated magnetic microspheres and preparation method thereof
By using a comb-like polyurethane-encapsulated magnetic microsphere preparation method, the leakage problem of superparamagnetic crystals or iron ions during use of magnetic microspheres is solved, the density and activity of functional groups are improved, non-specific adsorption is reduced, and better magnetic bead performance is achieved.
Patent Information
- Application Number
- CN202311412577.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, magnetic microspheres are prone to leaching superparamagnetic crystals or iron ions from magnetic microspheres during use, and the functional group density and activity are insufficient, resulting in excessive nonspecific adsorption.
Using a magnetic microsphere preparation method wrapped in comb polyurethane, an unsaturated linear polyurethane coating is formed by a mixed reaction of diisocyanate monomer and unsaturated diol monomer, and side chains are formed thereon to form a structure of a hydrophobic main chain and a hydrophilic side chain.
Effectively prevent iron ions from leaking, improve functional group density and activity, reduce non-specific adsorption, maintain appropriate particle size and surface area, and enhance the application effect of magnetic beads.
Smart Images

Figure CN119897077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and particularly relates to a comb-shaped polyurethane-wrapped magnetic microsphere and a preparation method thereof. Background Art
[0002] At present, magnetic microspheres are widely used in the fields of biology and medicine. For example, as drug carriers for drug delivery, for diagnostic purposes, immunoprecipitation and chemiluminescent immunoassay, etc., for protein purification, nucleic acid purification, cell separation and other transport carriers for target separation. In general, magnetic microspheres achieve the above functions by binding to the target through adsorption or covalent binding of functional groups on the surface. Adsorption and binding rely on the nonspecific adsorption force provided by the functional groups on the surface of polymer magnetic microspheres. For example, the functional group polythymine (Oligo dT) can specifically adsorb polyadenylic acid (PolyA), so polymer magnetic microspheres with Oligo dT functional groups on the surface specifically bind to mRNA with Poly A "tail" to separate mRNA from total RNA. Covalent binding relies on the reaction between the functional groups on the surface of polymer magnetic microspheres and the functional groups on proteins and antibodies. For example, polymer magnetic microspheres with active functional groups such as carboxyl or phenylmethylsulfonyl are often used in immunoassays to couple with amino groups in protein and antibody molecules. Polymer magnetic microspheres containing protein A and protein G coupled to proteins with affinity through active functional groups such as carboxyl or phenylmethylsulfonyl are used for affinity purification of antibodies, etc.
[0003] The widespread use of magnetic microspheres also puts forward higher requirements for them. First, the magnetic microspheres are required to be superparamagnetic and not permanently magnetized; second, the paramagnetic crystals are required to be tightly coated to prevent the superparamagnetic crystals or iron ions from leaching from the magnetic microspheres during use; third, there needs to be a hydrophilic spacer arm of sufficient density and length between the functional group and the coating film to ensure that nonspecific adsorption does not occur on the surface of the magnetic microspheres; fourth, the functional groups need to have sufficient density and activity, especially the magnetic microspheres whose surface functional groups provide adsorption force need to have sufficient functional group density, and the magnetic microspheres that rely on the surface functional groups to covalently bind proteins and antibodies need to have sufficient functional group activity.
[0004] Chinese patent document CN1849512A discloses a method for preparing coated magnetic particles, which discloses two polymer-coated polymer coating methods containing superparamagnetic crystal microspheres based on US patent document US 4654267, one is to use two epoxy compounds to react to form a polyether film layer to coat porous, surface functionalized, polymer microspheres containing superparamagnetic crystals; the other is to use diisocyanate and polyethylene glycol to react to obtain a polyurethane film layer to coat porous, surface functionalized, polymer microspheres containing superparamagnetic crystals. However, both of these coating methods have shortcomings: first, the polyether film layer formed by the epoxy compound can effectively prevent the magnetic crystals from being exposed or falling off and provide a hydrophilic connecting arm, but the film layer formed by the polyether has good hydrophilicity and cannot inhibit ion diffusion, limiting the application of polymer magnetic microspheres at lower pH. For example, after adsorbing antibodies, protein A magnetic beads are resolved at pH 3.0-3.5, and the use of polyether-coated protein A magnetic beads will cause iron ion leakage. The polyurethane film layer obtained by the reaction of diisocyanate and polyethylene glycol is relatively hydrophobic and can effectively prevent ion diffusion. At the same time, the polyethylene glycol used for chain extension provides a hydrophilic connecting arm of a certain length, but its active site is only distributed at one end of the macromolecular polyurethane, resulting in a low density of functional groups obtained in the next reaction. This problem limits the application of polymer magnetic microspheres in the adsorption and binding direction.
[0005] Chinese patent document CN108192007A has made some improvements on the basis of CN1849512A. Compared with CN1849512A, its synthesis method uses polyols or amino acids with carboxyl groups to extend the polyurethane with isocyanate terminal groups, introduce carboxyl groups on the linear polyurethane main chain, and increase the carboxyl density. However, since there is no spacer arm between the polyurethane main chain and the carboxyl group, there are problems such as low protein coupling efficiency and large nonspecific adsorption.
[0006] Japanese patent document JP2007127426A discloses a method for polymer coating magnetic microspheres, which uses two swelling polymerizations to coat polymer microspheres containing superparamagnetic crystals with hydrophobic and hydrophilic layers to solve the problems of magnetic crystal or ion leakage, low functional group density and linear polymer film swelling in solvents. Compared with CN1849512A, JP2007127426A uses swellable, porous polymer microspheres containing superparamagnetic crystals and hydrophobic acrylate or styrene monomers and crosslinking agents for the first swelling polymerization to form a hydrophobic film layer, which can effectively imitate magnetic crystal or ion leakage; and then uses hydrophilic or functional group-containing monomers and crosslinking agents for the second swelling polymerization, and the film layer provides sufficient hydrophilic connecting arms or functional groups. However, the coating method using two swelling polymerizations will increase the particle size of the polymer magnetic microspheres and reduce the surface area, affecting the application effect of the magnetic beads. For example, the polymer magnetic microspheres with increased particle size will have a low protein loading when used as protein carriers, and will have a low luminescence value when used for chemiluminescence immunoassays. In addition, in order to maintain a reasonable particle size and surface area, it uses template microspheres with a smaller particle size for two swelling polymerization coatings, which will significantly increase the difficulty of preparing the polymer magnetic microspheres. More importantly, the swelling polymerization method it uses will diffuse the monomer into the "template" microspheres. In order to ensure the coating effect, the weight ratio of the polymer used for "coating" to the "template" microspheres is much greater than that of CN1849512A, which only coats the surface of the microspheres. This will result in a reduced weight share of paramagnetic crystals and a poor magnetic response of the magnetic microspheres. Summary of the invention
[0007] Therefore, the technical problem to be solved by the present invention is that the superparamagnetic crystals or iron ions are easily leached from the magnetic microspheres during the use process in the prior art, the functional groups do not have sufficient density and activity, and non-specific adsorption is easily caused on the surface of the magnetic microspheres, thereby providing a comb-shaped polyurethane-wrapped magnetic microsphere and a preparation method thereof.
[0008] To this end, the present invention adopts the following technical solutions:
[0009] The present invention provides a method for preparing comb-shaped polyurethane-wrapped magnetic microspheres, comprising the following steps:
[0010] S1: mixing and reacting magnetic microspheres, diisocyanate monomers, and diol monomers including unsaturated diol monomers to obtain unsaturated linear polyurethane-coated magnetic microspheres;
[0011] S2: reacting the unsaturated bonds on the unsaturated linear polyurethane to generate side chains, thereby obtaining the magnetic microspheres wrapped by the comb-shaped polyurethane;
[0012] The reaction for generating the side chain is a polymerization reaction between a polymerizing agent and an unsaturated bond on the unsaturated linear polyurethane;
[0013] Alternatively, the reaction for generating the side chain is a coupling reaction between a coupling agent and an unsaturated bond on an unsaturated linear polyurethane.
[0014] Further, in step S1, the magnetic microspheres and diisocyanate monomers are first mixed and reacted, and then the diol monomer is added for reaction; the temperature of the magnetic microspheres and diisocyanate monomers is 0-100°C, the reaction time is 10-120min, the stirring speed is 50-300rpm, and the mass ratio of the magnetic microspheres to the diisocyanate monomers is 1:(0.1-10). Preferably, the reaction temperature is 20-50°C, the reaction time is 10-60min, and the mass ratio of the magnetic microspheres to the diisocyanate monomers is 1:(0.3-5).
[0015] The reactions carried out after adding the diol monomer include a first reaction and a second reaction;
[0016] The temperature of the first reaction is 40-120° C., the reaction time is 4-24 hours, the stirring speed is 50-300 rpm, and the molar ratio of the sum of the amount of the added diol monomer substance to the diisocyanate monomer is (0.1-0.5):1;
[0017] The temperature of the second reaction is 80-120°C, the reaction time is 1-8 hours, the stirring speed is 50-300rpm, and the molar ratio of the sum of the amount of diol monomers added to the diisocyanate monomers is (1-6): 1. Preferably, the temperature of the first reaction is 60-100°C, the reaction time is 16-24 hours, and the molar ratio of the sum of the amount of diol monomers added to the diisocyanate monomers is (0.2-0.3333): 1; the temperature of the second reaction is 80-100°C, the reaction time is 1-4 hours, and the molar ratio of the sum of the amount of diol monomers added to the diisocyanate monomers is (2-4): 1.
[0018] In the diol monomer, the molar ratio of the saturated diol monomer to the unsaturated diol monomer is (0-10 9 ):1, the preferred molar ratio is (0-10 6 ):1, the more preferred molar ratio is (0-10 3 ):1;
[0019] The molecular weights of the unsaturated diol monomer, the saturated diol monomer and the diisocyanate monomer are all less than 2000Da, preferably less than 1000Da, and more preferably 100-600Da. The molecular weight of the polyurethane macromolecule composed of the unsaturated diol monomer, the saturated diol monomer and the diisocyanate monomer is not less than 1KDa, and preferably the molecular weight of the polyurethane macromolecule is not less than 5KDa.
[0020] In step S2, when the reaction for generating the side chain is a polymerization reaction, the specific reaction is to react the polymerizer with an initiator and magnetic microspheres coated with unsaturated linear polyurethane at 20-90° C. for 2-24 hours, wherein the mass ratio of the magnetic microspheres coated with unsaturated linear polyurethane to the polymerizer is 1:(0.2-10), and the mass ratio of the polymerizer to the initiator is 1:(0:001-0.1);
[0021] When the reaction for generating side chains is a coupling reaction, the specific reaction is to react the coupling agent with the initiator unsaturated linear polyurethane coated magnetic microspheres at 20-80° C. for 2-24 hours, and the mass ratio of the unsaturated linear polyurethane coated magnetic microspheres to the coupling agent is 1:(0.001-10); the mass ratio of the coupling agent to the initiator is 1:(0:001-0.1).
[0022] Preferably, in step S2, when the reaction for generating the side chain is a polymerization reaction, the specific reaction is to react the polymerizer with the initiator and the magnetic microspheres coated with unsaturated linear polyurethane at 40-80° C. for 4-16 hours, the mass ratio of the magnetic microspheres coated with unsaturated linear polyurethane to the polymerizer is 1:(0.5-5), and the mass ratio of the polymerizer to the initiator is 1:(0:005-0.05);
[0023] When the reaction for generating side chains is a coupling reaction, the specific reaction is to react the coupling agent with the initiator unsaturated linear polyurethane coated magnetic microspheres at 40-70° C. for 4-16 hours, and the mass ratio of the unsaturated linear polyurethane coated magnetic microspheres to the coupling agent is 1:(0.001-0.1); the mass ratio of the coupling agent to the initiator is 1:(0:005-0.05).
[0024] The diisocyanate monomer is a compound having two isocyanate groups, including at least one of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDl), hexamethylene diisocyanate (HDI), and isophorone diisocyanate (IPDI); the most preferred ones are toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDl), and hexamethylene diisocyanate (HDI);
[0025] The unsaturated diol monomer is a diol having an unsaturated bond, preferably a diol having a double bond, including at least one of 2,4-hexadiene-1,6-diol, 2-pentene-1,5-diol, 1,4-butene diol, 2,3-dihydroxy-1-butene, 3-allyloxy-1,2-propylene glycol, and 2-vinyl propane-1,3-diol, and the most preferred one is at least one of 1,4-butene diol, 2,3-dihydroxy-1-butene, 2-vinyl propane-1,3-diol, and 3-allyloxy-1,2-propylene glycol;
[0026] The unsaturated diol monomer refers to a saturated diol, preferably a diol with a molecular weight of less than 600 Da, including at least one of diethanol, diethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol (polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600);
[0027] The polymerizing agent includes at least one of vinyl monomers, acrylic monomers, acrylate monomers, and acrylamide monomers; wherein the monomers used to synthesize carboxyl magnetic beads include: for example, acrylic acid, sodium acrylate, methacrylic acid, sodium methacrylate, 3-butenoic acid, 4-pentenoic acid, maleic acid, and 2-(prop-2-enoylamino)acetic acid;
[0028] Monomers used to synthesize amino magnetic beads: for example, allylamine hydrochloride, 4-penten-1-amine, 3-aminopropanol vinyl ether, 2-aminoethyl acrylate hydrochloride, 2-aminoethyl methacrylate hydrochloride, N-(2-aminoethyl)acrylamide, N-(3-aminopropyl)methacrylamide hydrochloride;
[0029] Monomers used to synthesize epoxy magnetic beads: for example, 1,2-epoxy-5-hexene, allyl glycidyl ether, 2,3-epoxypropyl acrylate, glycidyl methacrylate;
[0030] Monomers for synthesizing hydroxy magnetic beads: for example, allyl alcohol, butenol, 2-vinyloxyethanol, 2-vinyloxypropanol, hydroxyethyl acrylate, hydroxyethyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, N-(2-hydroxyethyl)acrylamide, N-(3-hydroxypropyl)acrylamide, N-(4-hydroxybutyl)acrylamide;
[0031] The coupling agent includes at least one of functionalized polyether, polyethylene glycol, polysaccharide, polypeptide, protein, nucleic acid or oligonucleic acid, preferably at least one of polyether, polyethylene glycol, polysaccharide, polypeptide, protein, nucleic acid or oligonucleic acid including thiol; wherein polyether, polyethylene glycol and polysaccharide are generally used as extension arms, and the hydrophilicity and hydroxyl structure are used to increase the coupling efficiency between the end group and the antibody; polypeptides and proteins use the thiol groups therein to directly complete the coupling;
[0032] The initiator includes at least one of an organic peroxide, an inorganic peroxide and an azo initiator. The organic peroxide includes acyl peroxides (benzoyl peroxide, lauroyl peroxide), hydroperoxides (isopropylbenzene hydroperoxide, tert-butyl hydroperoxide), dialkyl peroxides (di-tert-butyl peroxide, diisopropylbenzene peroxide), ester peroxides (tert-butyl perbenzoate, tert-butyl pervalerate), ketone peroxides (methyl ethyl ketone peroxide, cyclohexanone peroxide), dicarbonate peroxides (diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate); persulfates include potassium persulfate, sodium persulfate, and ammonium persulfate. Azo initiators include azobisisoheptanenitrile (ABVN), azobisisovaleronitrile, azobisisobutyronitrile, azobiscyclohexylcarbonitrile, azoisobutylcyanoformamide, azobisisobutylamidine hydrochloride, dimethyl azobisisobutyrate, azobisisobutylimidazoline hydrochloride, and azobiscyanovaleric acid.
[0033] The magnetic microspheres are porous, surface functionalized, and contain superparamagnetic crystals, and are prepared by any one of coprecipitation, oxidation precipitation, reduction precipitation, polymerization, or physical adsorption. The average particle size of the magnetic microspheres is 0.2-20 μm. The surface functionalized groups are at least one of hydroxyl, phenolic hydroxyl, ester, primary amine, secondary amine, urea, or amide groups, and the content of the groups is 10 -3 -10mmol / g;
[0034] The iron element in the superparamagnetic crystal accounts for 10-60wt% of the total mass of the magnetic microspheres in terms of mass percentage;
[0035] The specific surface area of the magnetic microspheres is 0.5-50m 2 / g, pore size is 5-50nm, porosity is 20-80%;
[0036] Preferably, the magnetic microspheres are prepared by any one of coprecipitation, oxidation precipitation or reduction precipitation; the average particle size of the magnetic microspheres is 0.5-10 μm; the surface functionalized groups are at least one of hydroxyl groups or amino groups, and the group content is 0.05-5 mmol / g; the iron element in the superparamagnetic crystal accounts for 20-50% of the total mass of the magnetic microspheres in terms of mass percentage; the specific surface area of the magnetic microspheres is 3-30 m 2 / g, pore diameter is 10-30nm, and porosity is 20-60%.
[0037] Before the reaction of step S1, the step of magnetically replacing the magnetic microspheres is also included. After the reaction of step S1, the step of washing and magnetic separation is also included. Specifically, the magnetic replacement is to add the magnetic microspheres into a reactor, and add anhydrous organic solvent into the reactor, disperse the magnetic microspheres in the anhydrous organic solvent by stirring, ultrasound, etc., reduce the water content in the system to below 1000ppm by multiple magnetic replacements, and finally adjust the weight ratio of the magnetic microspheres to the organic solvent to 1: (3-40); washing and magnetic separation are to wash the magnetic microspheres 3-10 times with one or more solvents or a mixture of solvents 3-40 times the weight of the microspheres, and magnetically separate after each washing to remove the unsaturated polyurethane that has not reacted with the magnetic microspheres;
[0038] Before the reaction of step S2, the step also includes the step of magnetically replacing the magnetic microspheres coated with unsaturated linear polyurethane. After the reaction of step S2, the step also includes the steps of washing and magnetic separation. Specifically, the magnetic replacement is to add the magnetic microspheres coated with unsaturated linear polyurethane into a reactor, add an organic solvent, water, an aqueous solution or a mixture of the above, disperse the magnetic microspheres in the above solution by stirring, ultrasound or the like, magnetically replace the solution 3-10 times, and finally adjust the weight ratio of the magnetic microspheres to the organic solvent to 1: (3-40); washing and magnetic separation are to wash the reacted magnetic microspheres 3-10 times with an organic solvent, water, an aqueous solution or a mixture of the above in an amount 3-40 times the weight of the microspheres, and magnetically separate after each washing to remove unreacted polymer.
[0039] The organic solvent refers to a solvent that does not react with isocyanate and is miscible with water in any proportion, preferably acetone, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and the most preferred ones are dioxane and diethylene glycol dimethyl ether. The water content is less than 200 ppm, preferably less than 100 ppm, and the most preferred water content is less than 50 ppm.
[0040] The aqueous solution is a buffer salt solution, and its purpose is pH buffering. The concentration is 10-1000mmol / L, and the pH range is 4-12. It is preferably a formic acid-formate aqueous solution, an acetic acid-acetate aqueous solution, a citric acid-citrate aqueous solution, a phosphoric acid-phosphate aqueous solution, a boric acid-borate aqueous solution, a 4-methylmorpholine-sodium hydroxide aqueous solution, and a tris(hydroxymethyl)aminomethane-hydrochloric acid aqueous solution. The most preferred are phosphoric acid-phosphate aqueous solution, a boric acid-borate aqueous solution, a 4-methylmorpholine-sodium hydroxide aqueous solution, and a tris(hydroxymethyl)aminomethane-hydrochloric acid aqueous solution. Its preferred concentration range is 20-200mmol / L, and the pH range is 5-10.
[0041] The present invention also provides a comb-shaped polyurethane-wrapped magnetic microsphere, which is prepared by the above preparation method, and the molecular weight of the side chain is not less than 200Da, preferably 200Da-100KDa, and more preferably 200-10KDa.
[0042] The technical solution of the present invention has the following advantages:
[0043] (1) The present invention uses comb-shaped polyurethane wrapped magnetic microspheres, whose hydrophobic polyurethane main chain can prevent iron ion leakage, and the hydrophilic side chain can obtain a more hydrophilic surface property or a higher ligand density. At the same time, the present invention prevents the excessive growth of the magnetic microspheres, controls the particle size of the magnetic microspheres, and prevents the excessive particle size from causing a reduction in surface area and a reduction in loading capacity.
[0044] (2) In the preparation process of the present invention, a polyurethane main chain containing double bonds is used to coat the magnetic particles. The double bonds on the main chain are used for further polymerization or grafting. The number of double bonds can adjust the side chain density. The raw materials and process changes of polymerization or grafting can adjust the side chain length. The length and density of the side chain can be adjusted to control the surface properties of the polymer magnetic microspheres.
[0045] (3) The comb-shaped polyurethane-wrapped magnetic microspheres prepared by the present invention through a specific preparation process have low iron ion leakage, high ligand density and appropriate particle size, reduce nonspecific adsorption, and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 is an electron microscope photograph of the polystyrene monodisperse microspheres obtained in Example 1;
[0048] Figure 2 is an electron microscope photograph of the magnetic microspheres obtained in Example 8;
[0049] Figure 3 is an electron microscope photograph of the unsaturated linear polyurethane-coated magnetic microspheres obtained in Example 10;
[0050] Figure 4 This is an electron microscope photograph of the comb-shaped polyurethane-wrapped magnetic microspheres obtained in Example 10. DETAILED DESCRIPTION
[0051] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0052] The analysis conditions in the examples are as follows:
[0053] The drying loss of magnetic microspheres is tested by Mettler Rapid Moisture Analyzer HX204. 0.3-3.0g of magnetic microspheres are placed in Mettler Rapid Moisture Analyzer HX204, the test temperature is set to 110℃, and the test time is unlimited. The drying loss is measured under this condition.
[0054] The specific surface area of the magnetic microspheres was measured by nitrogen adsorption method. That is, 0.1500-0.2000 g of the dried polymer microspheres were accurately weighed and placed in the fully automatic specific surface and porosity analyzer ASAP 2020 (Micromeritics Instrument Co.), and the specific surface area was set to be detected with an air intake speed of 5-10 KPa. Under this condition, the specific surface area was detected by nitrogen physical adsorption method and the specific surface area was calculated by BET model.
[0055] The average pore size and porosity of the magnetic microspheres were measured by mercury intrusion, that is, 0.1500-0.3000 g of sample was accurately weighed and placed in an automatic mercury intrusion instrument AutoPore IV 9500 (Micromeritics Instrument Co.), and the contact angle of mercury was set to 130°, and the porosity was measured by mercury intrusion under this condition.
[0056] The iron content of magnetic microspheres was detected by ion chromatography. 5.00±1.00 mg of magnetic microspheres were accurately weighed and soaked in 100.0 mL of concentrated nitric acid for 24 hours. 10.00 mL of supernatant was magnetically aspirated and diluted 10 times. The Fe3+ ion external standard method was used for detection using the ICP-MS6880 inductively coupled plasma mass spectrometer from Meixi. According to the linear relationship of the external standard method, the iron ion concentration detected was within the linear range of 0-50000 ppb, which was the effective iron ion concentration, and the iron content of the magnetic crystals in the magnetic microspheres was calculated based on the concentration.
[0057] Detection of nitrogen content of magnetic microspheres:
[0058] The nitrogen content of the magnetic microspheres was detected by elemental analysis. 0.1500-0.3000 g of magnetic microspheres were weighed and placed in the Vario ELⅢ elemental analyzer of the German Elementar Company. The CHN mode was selected and the trace combustion method was used to automatically determine and calculate the nitrogen content.
[0059] Determination of the double bond group content of magnetic microspheres:
[0060] The determination of the double bond group content of the magnetic microspheres is to first allow the thiol to undergo a click chemistry reaction with the unsaturated double bonds on the magnetic microspheres, introduce the sulfur element into the magnetic microspheres, and then detect it by elemental analysis. Specifically, 0.2-0.4g of magnetic microspheres are weighed, mixed with 10 times the weight of mercaptoethanol, 2 times the weight of azobisisobutyronitrile, and 20 times of isopropanol, and placed on a 70-degree Celsius shaker for reaction for 24 hours. After the reaction, isopropanol, water, and ethanol are used to wash 5-10 times, and the microspheres are vacuum dried. Then 0.1500-0.3000g of the above magnetic microspheres are weighed and placed in the Vario ELⅢ elemental analyzer of Elementar Company of Germany, the CHNS mode is selected, and the sulfur content is automatically determined and calculated by the micro-combustion method. Finally, the content of double bond groups is calculated based on the sulfur content of the magnetic microspheres.
[0061] Determination of the content of hydroxyl or phenolic hydroxyl groups in magnetic microspheres:
[0062] The hydroxyl group content or phenolic hydroxyl group content of the magnetic microspheres is determined by the method of the national standard GB-T 12008.3-2008 "Plastic polyether polyols Part 3 Determination of hydroxyl value".
[0063] Determination of carboxyl group content of magnetic microspheres
[0064] The carboxyl group content of the magnetic microspheres was measured by conductometric titration using 794 Basic Titrino manufactured by Metrohm.
[0065] Determination of the epoxy group content of magnetic microspheres The epoxy group content of magnetic microspheres can be determined by calculating the amount of equivalent sodium hydroxide produced by the reaction of sodium thiosulfate with epoxy groups. Specifically, 100 mg of the surface epoxidized magnetic microspheres were washed three times with 1 mL of pure water, then rotated and stirred in 1 mL of 1.0 M sodium thiosulfate for 24 hours, and the generated sodium hydroxide was titrated with 10.0 mM standard hydrochloric acid using a Mettler automatic potentiometric titrator T5.
[0066] Determination of the tosyl content of magnetic microspheres:
[0067] Determination of tosyl content of magnetic microspheres: It can be calculated by the amount of equivalent p-toluenesulfonic acid produced by the reaction of ethanolamine and tosyl groups. Specifically, 100 mg of magnetic microspheres with tosyl groups on the surface were washed three times with 1 mL of pure water, and then stirred in 1 mL of 1.0 M ethanolamine for 24 hours to separate p-toluenesulfonic acid from the surface of the magnetic polymer. The absorbance at 261 nm (ε=331) in the resulting solution was measured from the supernatant.
[0068] Determination of protein A content in magnetic microspheres
[0069] The content of protein A bound to magnetic microspheres was quantified in the following manner: 2 mL of human IgG 2.5 mg / mL was reacted with 5.0 mg of protein A-bound magnetic microspheres in a centrifuge tube, and the amount of IgG remaining in the supernatant was measured at 280 nm using a Thermo Scientific NanoDropOne microspectrophotometer.
[0070] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional experimental steps or conditions described in the literature in the art.
[0071] The following specific examples are further explanations of the present invention. The examples cited cannot list all the embodiments of the present invention. Only some of the embodiments are used as examples for explanation. The specific examples are as follows:
[0072] Example 1
[0073] This example is the preparation of 500nm polystyrene monodisperse microspheres.
[0074] 3.00 kg of styrene was washed twice with 2 L of 4% (w / v) sodium hydroxide, and then washed with water to pH 7.8. 300 g of anhydrous sodium sulfate was added and distilled under reduced pressure at 100 mBar and 50°C. 1.80 kg of the intermediate fraction was collected and sealed and dried at -20°C for storage.
[0075] 12g of sodium dodecyl sulfate was added to 14.40kg of water, stirred to dissolve, and filtered using a 0.22μm filter membrane. The filtered solution was added to a 20L reactor and purged with nitrogen, and deoxygenated by ultrasonication for 30 minutes. Then 1.60kg of the above-mentioned styrene was added, stirred at 240rpm and heated to 80°C. After reaching 80°C, 160mL of 10% (w / v) ammonium persulfate solution was added, and the reaction was maintained at 80°C for 24h to obtain a 500nm polystyrene monodisperse microsphere suspension. The structure of the polystyrene monodisperse microsphere is as shown in Figure 1 shown.
[0076] Example 2
[0077] This example is the preparation of 1 μm monodisperse porous polystyrene microspheres.
[0078] 2.35 kg of 80% divinylbenzene, 1.40 kg of styrene, 8.25 kg of toluene, and 37.5 g of benzoyl peroxide were mixed and dissolved, and 1% polyvinyl alcohol (PVA 1788) and 60 L of 0.45% sodium dodecyl sulfate solution were added, and finely emulsified with an ultrasonic disperser. After emulsification, 6.0 kg of the 500 nm particle size polystyrene monodisperse microsphere suspension of Example 1 was added, which contained 0.60 kg of 500 nm polystyrene monodisperse microspheres. After stirring at 30°C for 16 hours, the mixture was polymerized at 80°C for 20 hours. The microspheres were washed with water and acetone and dried. 3.51 kg of monodisperse porous polystyrene microspheres were obtained, and the specific surface area was 550 m 2 / g, the average particle size detected by the image particle method is 0.93μm, and the average pore size detected by the mercury injection method is 16nm.
[0079] Example 3
[0080] This example is the preparation of 1 μm monodisperse porous nitrated polystyrene microspheres.
[0081] Add 3.0 kg of monodisperse porous polystyrene microspheres obtained in Example 2 to a 100 L reactor, add 75 kg of dichloromethane, stir (70 rpm), control the temperature to -10 ° C, pass nitrogen for 30 minutes, then add 1.50 kg of 98% concentrated sulfuric acid and 1.50 kg of 68% concentrated nitric acid. Heat to 25 ° C and react for 4 hours. After the reaction is completed, cool to -10 ° C and add an ice-water mixture to the reactor. Wash the microspheres with acetone and water. Obtain 9.13 kg of monodisperse porous nitrated polystyrene microspheres with a water content of 66.7%. The nitrogen content in the microspheres was detected to be 6.2% by elemental analysis.
[0082] Example 4
[0083] This example is the preparation of 1 μm monodisperse porous polyacrylate microspheres.
[0084] 1.88 kg of trimethylolpropane trimethacrylate, 1.87 kg of glycidyl methacrylate, 8.25 kg of amyl acetate and 37.5 g of azobisisobutyronitrile were mixed and dissolved, and 1% (m / m) polyvinyl alcohol (PVA 1877) and 60 L of 0.45% (m / m) sodium dodecyl sulfate solution were added, and finely emulsified with an ultrasonic disperser. After emulsification, 6.0 kg of a suspension of polystyrene monodisperse microspheres with a particle size of 500 nm of Example 1 was added, which contained 0.60 kg of polystyrene monodisperse microspheres. After stirring at 30°C for 16 hours, the suspension was polymerized at 80°C for 20 hours. The microspheres were washed with water and acetone and dried. 3.21 kg of monodisperse porous polyacrylate microspheres were obtained, and the specific surface area was 370 m 2 / g, the particle size of image particle detection is 0.96μm, and the average pore size of mercury intrusion detector is 25nm.
[0085] Example 5
[0086] This example is the preparation of 1 μm monodisperse porous hydroxylated polyacrylate microspheres.
[0087] 3.0 kg of monodisperse porous polyacrylate microspheres obtained in Example 4 were added to a 50 L reactor, and 30 L of 1% (m / v) sulfuric acid solution was added, and stirred at 40° C. for 6 hours. After the reaction was completed, the microspheres were washed with water and methanol to obtain 2.65 kg of monodisperse porous hydroxylated polyacrylate microspheres. The hydroxyl content in the polymer microspheres was 1.77 mmol / g (dry) using the national standard GB / T 12008.3-2009.
[0088] Example 6
[0089] This example is the preparation of 1 μm monodisperse porous amino polystyrene microspheres.
[0090] 3.0 kg of monodisperse porous nitrated polystyrene microspheres with a water content of 66.7% obtained in Example 3 were added to a 50 L reactor, and 30 L of 5.0% (m / v) stannous chloride solution was added, and stirred at 80° C. for 6 hours. After the reaction was completed, the microspheres were washed with water to obtain 2.75 kg of monodisperse porous amino polystyrene microspheres with a water content of 65.3%.
[0091] Example 7
[0092] This example is a co-precipitation method for preparing 1 μm magnetic microspheres.
[0093] 2.88 kg of monodisperse porous amino polystyrene microspheres with a water content of 65.3% obtained in Example 6 and 24 kg of water were added to a 50 L reactor, nitrogen was passed, stirred and cooled to 0 ° C. 1.60 kg of ferric chloride hexahydrate and 1.07 kg of ferrous chloride tetrahydrate were added to the reactor. Stirring was continued for 30 minutes and maintained at 0 ° C. 4.5 kg of 25% concentrated ammonia was added, and the temperature was raised to 60 ° C for 2 hours. The reaction solution was cooled to room temperature, centrifuged, washed with water, methanol and dried to obtain magnetic microspheres. The iron content in the microspheres was detected to be 32.4% by ion chromatography.
[0094] Example 8
[0095] This example is about preparing 1 μm magnetic microspheres by oxidation precipitation method.
[0096] 3.00 kg of monodisperse porous nitrated polystyrene microspheres with a water content of 66.7% obtained in Example 3 and 24.0 kg of water were added to a 50 L reactor, nitrogen was passed through at room temperature, and stirred for 30 minutes. Then 3.10 kg of ferrous sulfate heptahydrate (FeSO4.7H2O) was added to the reactor and stirred for 30 minutes. 4.5 kg of 25% concentrated ammonia water was added, and the temperature was raised to 60°C for 2 hours. The reaction solution was cooled, centrifuged, and the particles were washed with water and methanol and dried to obtain magnetic microspheres. The iron content in the microspheres was detected by ion chromatography and was 36.4%. The structure of the magnetic microspheres is as shown in FIG. Figure 2 shown.
[0097] Example 9
[0098] This example is a hydrothermal method for preparing 1 μm magnetic microspheres.
[0099] 1.0 kg of monodisperse porous hydroxylated polyacrylate microspheres obtained in Example 5 were added to a 50 L reactor, and then 24 kg of ethylene glycol was added to the reactor, nitrogen was passed through at room temperature, and stirred for 30 minutes, and then 5.42 kg of ferric chloride hexahydrate, 180 g of sodium acetate and 361 g of polyethylene glycol (MW = 6000) were added thereto, and the temperature was raised to 60 ° C and stirred for 16 hours; the reactor was heated to 200 ° C and reacted for 12 hours; after the reaction was completed, the temperature was lowered to room temperature, and the particles were washed with water and methanol by centrifugation and dried to obtain magnetic microspheres. The iron content in the microspheres was 34.7% using ion chromatography.
[0100] Example 10
[0101] This example is the preparation of magnetic microspheres (carboxyl) wrapped by comb-shaped polyurethane.
[0102] (1) Add 50g of the magnetic microspheres obtained in Example 8 and 1.0kg of anhydrous diethylene glycol dimethyl ether to a 5L reactor, purge with nitrogen at room temperature, and stir for 5 minutes. Recover the magnetic microspheres by magnetic attraction, and continue to wash with anhydrous diethylene glycol dimethyl ether twice to remove moisture from the reaction solution. Finally, adjust the concentration of the magnetic microsphere solution to 5wt% by magnetic attraction, purge with nitrogen at room temperature, and stir for 30 minutes. Then add 250g of diphenylmethane diisocyanate (MDI) and continue stirring for 30 minutes. Then add 26.5g of anhydrous 1,2-dihydroxy-3-butene and heat it to 70°C and continue to pass nitrogen and stir for 16 hours. Then add 133.5g of anhydrous 1,2-dihydroxy-3-butene and 450g of anhydrous polyethylene glycol 300 (PEG300) and heat it to 80°C. Continue stirring for 4 hours. After the reaction is completed, cool it to room temperature. Recover the magnetic microspheres coated with unsaturated linear polyurethane through a magnet, wash the particles with diethylene glycol dimethyl ether, acetone, and isopropanol, and dry them in a vacuum. The specific surface area detected by nitrogen adsorption is 14.4m 2 / g, click chemistry-elemental analysis method detected its double bond content was 73μmol / g; the structure of the magnetic microspheres coated with unsaturated linear polyurethane is as follows Figure 3 As shown, it can be seen that, and Figure 2 In contrast, the microspheres coated with unsaturated polyurethane caused local bulges on the surface;
[0103] (2) Add 15g of unsaturated linear polyurethane-coated magnetic microspheres and 300g of isopropanol to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes. , to remove oxygen from the reaction solution. Then add 30g of acrylic acid and 1g of azobisisobutyronitrile (AIBN) and continue stirring for 30 minutes. Raise the temperature to 70°C and continue passing nitrogen and stirring for 16 hours; after the reaction, cool to room temperature, recover the magnetic microspheres with a magnet, and wash the particles with isopropanol and water. The carboxyl content was detected by conductivity titration, and the carboxyl content was 1593μmol / g. The image particle method detected that the average particle size was 1.03μm, and the structure of the comb-shaped polyurethane-coated magnetic microspheres is as follows Figure 4 As shown, we can see that Figure 3 In comparison, the side chains formed by surface polymerization make the surface of the microspheres rougher.
[0104] Embodiment 11
[0105] This example is the preparation of magnetic microspheres (carboxyl) wrapped by comb-shaped polyurethane.
[0106] (1) Add 50g of the magnetic microspheres obtained in Example 7 and 1.0kg of anhydrous diethylene glycol dimethyl ether to a 5L reactor, purge with nitrogen at room temperature, and stir for 5 minutes. Recover the magnetic microspheres by magnetic attraction, and continue to wash with anhydrous diethylene glycol dimethyl ether twice to remove moisture from the reaction solution. Finally, adjust the concentration of the magnetic microsphere solution to 5wt% by magnetic attraction, purge with nitrogen at room temperature, and stir for 30 minutes. Then add 250g of hexamethylene diisocyanate (HDI) and continue stirring for 30 minutes. Then add 29.5g of anhydrous 3-allyloxy-1,2-propylene glycol and 44.6g of anhydrous polyethylene glycol 200 (PEG200), heat to 80°C and continue nitrogen flow and stirring for 16h; then add 295g of anhydrous 3-allyloxy-1,2-propylene glycol and 892g of anhydrous polyethylene glycol 400 (PEG400), heat to 100°C, continue stirring for 4h, cool to room temperature after the reaction, recover the unsaturated linear polyurethane-coated magnetic microspheres through a magnet, wash the particles with diethylene glycol dimethyl ether, acetone, and isopropanol, and dry them in vacuum. The specific surface area detected by nitrogen adsorption is 12.7m 2 / g, and the double bond content was 41μmol / g as determined by click chemistry-elemental analysis;
[0107] (2) Add 15g of unsaturated linear polyurethane-coated magnetic microspheres and 300g of isopropanol to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 60g of acrylic acid and 1g of azobisisobutyronitrile (AIBN) and continue stirring for 30 minutes. Heat to 80°C and continue passing nitrogen and stirring for 12 hours. After the reaction is completed, cool to room temperature, recover the magnetic microspheres with a magnet, and wash the particles with isopropanol and water. The carboxyl content was detected by conductivity titration, and the carboxyl content was 1470μmol / g. The average particle size was 1.05μm by image particle method.
[0108] Example 12
[0109] This example is the preparation of magnetic microspheres (carboxyl) wrapped by comb-shaped polyurethane.
[0110] (1) Add 50 g of the magnetic microspheres obtained in Example 9 and 1.0 kg of anhydrous dioxane to a 5 L reactor, pass nitrogen at room temperature, and stir for 5 minutes. Recover the magnetic microspheres by magnetic attraction, and continue to wash with anhydrous dioxane twice to remove moisture from the reaction solution. Finally, adjust the concentration of the magnetic microsphere solution to 5 wt % by magnetic attraction, pass nitrogen at room temperature, and stir for 30 minutes. Then add 250g toluene diisocyanate (TDI) and continue stirring for 30 minutes. Then add 21.9g anhydrous 2-vinyl propane-1,3-diol and 13.3g anhydrous ethylene glycol, warm to 70°C and continue nitrogen flow and stirring for 16h. Then add 219g anhydrous 2-vinyl propane-1,3-diol, 215g anhydrous polyethylene glycol 200 (PEG200), 430g anhydrous polyethylene glycol 400 (PEG400) and heat to 80°C. Continue stirring for 4h. After the reaction is completed, cool to room temperature. Recover the magnetic microspheres coated with unsaturated linear polyurethane by magnet, wash the particles with dioxane, acetone and isopropanol and dry in vacuum. The specific surface area detected by nitrogen adsorption method is 11.9m 2 / g, and the double bond content was 57μmol / g as determined by click chemistry-elemental analysis;
[0111] (2) Add 15g of unsaturated linear polyurethane-coated magnetic microspheres and 300g of 150μm sodium dihydrogen phosphate aqueous solution with a pH of 7.8 to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 45g of sodium acrylate and continue stirring for 30 minutes. Finally, add 1g of sodium persulfate and heat to 70°C and continue passing nitrogen and stirring for 16 hours. After the reaction is completed, cool to room temperature, recover the magnetic microspheres with a magnet, and wash the particles with water. The carboxyl content was detected by conductivity titration, and the carboxyl content was 1268μmol / g. The average particle size was detected by the image particle method and was 1.09μm.
[0112] Example 13
[0113] This example is the preparation of comb-shaped polyurethane-wrapped magnetic microspheres (epoxy group).
[0114] (1) preparing magnetic microspheres coated with unsaturated linear polyurethane by the same method as in Example 10;
[0115] (2) Add 15g of unsaturated linear polyurethane-coated magnetic microspheres and 300g of isopropanol to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 45g of allyl glycidyl ether and continue stirring for 30 minutes. Finally, add 1g of azobisisobutyronitrile (AIBN) and heat to 70°C and continue passing nitrogen and stirring for 16 hours. After the reaction is completed, cool to room temperature, recover the magnetic microspheres with a magnet, and wash the particles with water. The epoxy group content is detected by sodium thiosulfate-point titration method, and the epoxy content is 128μmol / g.
[0116] Embodiment 14
[0117] This example is the preparation of comb-shaped polyurethane-wrapped magnetic microspheres (epoxy group).
[0118] (1) preparing magnetic microspheres coated with unsaturated linear polyurethane by the same method as in Example 11;
[0119] (2) Add 15g of unsaturated linear polyurethane coated magnetic microspheres and 300g of dimethylformamide to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 45g of glycidyl methacrylate and continue stirring for 30 minutes. Finally, add 1g of azobisisobutyronitrile (AIBN) and heat to 70°C and continue passing nitrogen and stirring for 16 hours. After the reaction is completed, cool to room temperature, recover the magnetic microspheres with a magnet, and wash the particles with water. The epoxy group content is detected by sodium thiosulfate-point titration method, and the epoxy content is 163μmol / g.
[0120] Embodiment 15
[0121] This example is the preparation of comb-shaped polyurethane-wrapped magnetic microspheres (epoxy group).
[0122] (1) preparing magnetic microspheres coated with unsaturated linear polyurethane by the same method as in Example 12;
[0123] (2) Add 15g of unsaturated linear polyurethane-coated magnetic microspheres and 300g of tetrahydrofuran to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 45g of glycidyl methacrylate and continue stirring for 30 minutes. Finally, add 1g of azobisisoheptanenitrile (AIBN) and heat to reflux, and continue passing nitrogen and stirring for 16 hours; after the reaction is completed, cool to room temperature, recover the magnetic microspheres with a magnet, and wash the particles with water. The epoxy group content is detected by sodium thiosulfate-point titration method, and the epoxy content is 152μmol / g.
[0124] Example 16
[0125] This example is the preparation of comb-shaped polyurethane-wrapped magnetic microspheres (hydroxyl).
[0126] (1) preparing magnetic microspheres coated with unsaturated linear polyurethane by the same method as in Example 10;
[0127] (2) Add 15g of unsaturated linear polyurethane coated magnetic microspheres and 300g of water to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 15g of N-(2-hydroxyethyl) acrylamide, continue stirring for 30 minutes, and finally add 0.5g of potassium persulfate and heat to 60°C and continue passing nitrogen and stirring for 16 hours; after the reaction is completed, cool to room temperature, recover the magnetic microspheres through a magnet, wash the particles with water and methanol, and vacuum dry. The hydroxyl content was detected using the national standard GB-T12008.3-2008 "Determination of hydroxyl value of plastic polyether polyols Part 3" method, and the hydroxyl content was 1154μmol / g.
[0128] Embodiment 17
[0129] This example is the preparation of comb-shaped polyurethane-wrapped magnetic microspheres (hydroxyl).
[0130] (1) preparing magnetic microspheres coated with unsaturated linear polyurethane by the same method as in Example 10;
[0131] (2) Add 15g of unsaturated linear polyurethane coated magnetic microspheres and 300g of water to a 1L reactor, pass nitrogen at room temperature, and stir for 30 minutes to remove oxygen from the reaction solution. Then add 5g of mercapto polyethylene glycol 400 (OH-PEG400-SH) and continue stirring for 30 minutes. Finally, add 1.5g of azobisisobutyronitrile (AIBN) and heat to 70°C and continue passing nitrogen and stirring for 16 hours. After the reaction is completed, cool to room temperature, recover the magnetic microspheres through a magnet, wash the particles with water and methanol, and vacuum dry. The hydroxyl content was detected using the national standard GB-T 12008.3-2008 "Determination of hydroxyl value of plastic polyether polyols Part 3" method, and the hydroxyl content was 154μmol / g.
[0132] Comparative Example 1
[0133] This comparative example adopts the coating method of CN1849512A to prepare carboxyl magnetic beads. Specifically:
[0134] 13.3 g of the magnetic microspheres prepared in Example 8 (wherein the surface of the particles is functionalized by nitration and reduction and contains superparamagnetic iron oxide) were washed 5 times with 93 g of diethylene glycol dimethyl ether, the dry matter of the particles in diethylene glycol dimethyl ether was adjusted to a weight ratio of 15%, and 3.07 g of glycidol, 8.06 g of 1,4-butanediol diglycidyl ether and 5.68 g of glycidyl methacrylate were added to the particles. The mixture was heated to 75°C and stirred for 20 hours. The particles were then washed 6 times with 70 g of methanol and 4 times with 80 g of isopropanol. The particle content (based on dry matter) was adjusted to a weight ratio of 24%, and methanol (24 g), acrylic acid (9.64 g) and 2,2'-azoisobutyronitrile (0.41 g) were added to the suspension. The mixture was heated to 73-75°C and stirred for 20 hours. The particles were then washed 6 times with 73 g of methanol and once with 94 g of 0.15 M NaOH. The dry matter of the mixture of particles and 0.15 M NaOH was adjusted to 12 wt%, and the mixture was heated to 75° C. and stirred for 3.5 hours. The particles were washed 3 times with 99 g of water and 5 times with 99 g of 0.01 M NaOH. The carboxyl content was 321 μmol / g using the conductometric titration method, and the average particle size was 0.98 μm using the image particle method.
[0135] Comparative Example 2
[0136] This comparative example adopts the coating method of CN1849512A to prepare tosyl magnetic beads. Specifically:
[0137] To 100 mL of the reaction mixture, 5.0 g of the magnetic microspheres prepared in Example 8 (wherein the particle surface is functionalized by nitration and reduction and contains superparamagnetic iron oxide) were added, 26.82 g of diethylene glycol dimethyl ether suspension was added, Desmodur VL (18.34 g) and ethylene glycol (1.64 g) were added. The mixture was heated at 80° C. and stirred for 20 hours. A mixture of ethylene glycol (27.29 g) and 1,4-diazabicyclo (2.2.2) octane (0.66 g) was added to the particle suspension. The mixture was heated at 80° C. and stirred for 1 hour. The particles were cooled and washed 3 times with 100 g of diethylene glycol dimethyl ether and 4 times with 100 g of acetone. To the above 17.1 g of acetone suspension, p-toluenesulfonyl chloride (16 g) and pyridine (7.85 g) were added. The mixture was stirred at 25° C. for 17 hours. The particles were then washed 3 times with 50 ml of acetone, 1 time with 50 ml of a water mixture of 80 wt % acetone, 1 time with 50 ml of a water mixture of 60 wt % acetone, 1 time with 50 ml of a water mixture of 30 wt % acetone, and 3 times with 50 ml of water. Tosyl magnetic beads were obtained. The tosyl group content was 51 μmol / g using UV colorimetry, and the average particle size was 1.02 μm using an image particle method.
[0138] Comparative Example 3
[0139] This comparative example adopts the coating method of patent CN 108192007A to prepare carboxyl magnetic beads, specifically:
[0140] 5.0 g of the magnetic microspheres prepared in Example 8 (wherein the surface of the particles is functionalized by nitration and reduction and contains superparamagnetic iron oxide) were added to 100 mL of the reaction mixture, dispersed in 60 mL of acetone, the flask was sealed and nitrogen was passed through for 10 min, 250 mg of MDI was dissolved in 6 mL of acetone, added to the flask, and reacted at 80° C. for 2 hours. Finally, 200 μL of triethylene glycol, 400 μL of PEG 800, and 500 mg of MDI were dissolved in 6 mL of acetone, added to the flask, and the reaction conditions were 80° C., nitrogen was passed through, and stirred overnight for 20 hours; the next day, 1 g of 2,2-bis(hydroxymethyl)propionic acid and 250 mg of MDI were dissolved in 5 mL of acetone, added to the flask, and the reaction was continued for 6 hours, and finally washed repeatedly with ethanol and water to prepare carboxyl polyurethane-coated magnetic microspheres of about 1 μm. The carboxyl group content was measured by conductivity titration and found to be 951 μmol / g. The average particle size was measured by image particle method and found to be 1.02 μm.
[0141] Test Example 1
[0142] Take 100 mg of the products prepared in Comparative Example 1, Examples 10, 11, and 12, respectively, and soak them in 10 mL of 100 mM glycine-hydrochloric acid (Glycine-HCL) pH 3.0 solution. Shake on a shaker at 25°C and 45 rpm for 2 hours, take 5 mL of the supernatant, add 5 mL of 10% nitric acid, and use ICP to detect the concentration of trivalent iron ions, and calculate the iron leakage (ppm) (ng Fe / mg magnetic beads).
[0143] The particle size, carboxyl content and iron leakage of the products obtained in Comparative Example 1 and Examples 10, 11 and 12 are shown in the following table:
[0144] Table 1 Particle size, carboxyl content and iron leakage of Comparative Example 1 and Examples 10, 11, 12
[0145]
[0146] Test Example 2
[0147] (1) 5 g of magnetic microspheres with epoxy groups on the surface obtained in Examples 13, 14, and 15 were added to a 250 mL reactor, 50 mL of water was added thereto, and the mixture was stirred for 30 minutes. Then 50 mL of 1% sulfuric acid was added, and the mixture was heated to 40°C for reaction for 1 hour. After the reaction, the mixture was cooled to room temperature, and the magnetic microspheres were recovered by a magnet. The particles were washed with water and methanol, and vacuum dried to obtain magnetic microspheres (hydroxyl) coated with comb-shaped polyurethane, which were recorded as Example 13', Example 14', and Example 15'. The hydroxyl content was detected using the national standard GB-T12008.3-2008 "Determination of hydroxyl value of plastic polyether polyols Part 3" method, and the hydroxyl content was 1047 μmol / g, 954 μmol / g, and 923 μmol / g, respectively.
[0148] (2) The comb-shaped polyurethane-wrapped magnetic microspheres (hydroxyl) of Example 16, Example 13', Example 14', and Example 15' were added to a 100 mL reactor, 50 mL of pyridine was added thereto respectively, and the mixture was stirred for 30 minutes, and then 1.0 g of p-toluenesulfonyl chloride was added. The mixture was heated to 40°C for 2 hours and then cooled to room temperature. The magnetic microspheres were recovered by a magnet, and the particles were washed with acetone, methanol, and water to obtain toluenesulfonyl magnetic beads. The toluenesulfonyl group content was detected by the p-toluenesulfonic acid UV method, and the contents were 1021 μmol / g, 957 μmol / g, 884 μmol / g, and 901 μmol / g, respectively. The average particle size detected by the image particle method was 1.08, 1.03, 1.04, and 1.06 μm.
[0149] (3) Comparing the tosyl magnetic beads obtained in comparative example 2 with those obtained in step (2), the particle size and tosyl content are shown in the following table:
[0150] Table 2 Tosyl magnetic beads particle size and tosyl content
[0151]
[0152] It can be seen from the above table that the comb-shaped polyurethane coated magnetic microspheres of the present invention increase the density of the functional group hydroxyl or the toluenesulfonyl group obtained by further coupling compared with the coating method of the linear polyurethane in CN1849512A.
[0153] Test Example 3
[0154] (1) Take 50 mg of the comb-shaped polyurethane-coated magnetic microspheres prepared in Examples 10, 11, and 12, respectively, add 3 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6, mix thoroughly, separate magnetically and discard the supernatant, repeat twice; resuspend the magnetic beads in 0.75 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6, add 100 mg / ml 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 50 mg / ml N-hydroxysuccinimide (NHS) dissolved in 0.25 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6, blow evenly, put on a shaker (220 rpm, 30° C.) and shake for 30 min; separate magnetically and discard the supernatant, resuspend the magnetic beads in 3 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6, separate magnetically and discard the supernatant again, and 1 ml 20mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6, resuspend the magnetic beads for use; add 0.1ml protein A (Protein A) (25mg / ml) to 1.9ml, mix well, mix the magnetic beads in step 3 and add them to the diluted protein A (Protein A), put them on a shaker (220rpm, 30℃) and shake for 4h; add 0.3ml 10% BSA, 2% Gly, 20mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, 0.1% ProClin300, pH: 5.6, put them on a shaker (220rpm, 30℃) and continue to shake for 1h; after magnetic separation and discarding the supernatant, wash them 3 times with 0.1M sodium hydroxide and 6 times with water to obtain protein A magnetic beads. The protein A magnetic bead coupling amount was detected by IgG, and the protein A content was 43.4 mg / g, 42.5 mg / g, and 43.7 mg / g respectively. The average particle size was 1.10, 1.13, and 1.18 μm by the image particle method;
[0155] (2) The carboxyl magnetic beads of comparative example 1 were used to prepare protein A magnetic beads by the coupling method in step (1). The coupling amount of protein A magnetic beads was detected by IgG, and the protein A content was 20.7 mg / g. The average particle size was 1.04 μm by the image particle method;
[0156] (3) Take 10.0 mg of the above protein A magnetic beads and soak them in 1.0 mL of 100 mM glycine-hydrochloric acid (Glycine-HCL) pH 3.0 solution. Shake at 25°C 45 rpm for 2 h. Take 0.5 mL of the supernatant and add 0.5 mL of 10% nitric acid to detect the concentration of trivalent iron ions using ICP, and calculate the iron leakage (ppm) (ng Fe / mg magnetic beads).
[0157] The particle size, carboxyl content and iron leakage of the protein A magnetic beads obtained in comparative example 1 and examples 10, 11 and 12 are compared as shown in the following table:
[0158] Table 3 Protein A magnetic beads particle size, carboxyl content and iron leakage
[0159]
[0160] It can be seen from Table 1 and Table 3 that the comb-shaped polyurethane coated magnetic microspheres of the present invention increase the density of the functional group carboxyl or the group of protein A obtained by further coupling compared with the polyether polymer coating method synthesized from the epoxy compound of CN1849512A, and reduce the leakage of iron ions.
[0161] From the coating effects of Examples 10, 11, 12 and protein A and toluenesulfonyl, it can be seen that the particle size increase of the magnetic microspheres coated with comb-shaped polyurethane described in the present invention is within 25% compared with the swelling method used in JP2007127426, which is less than the particle size increase of 100-300% disclosed in JP2007127426.
[0162] Test Example 4
[0163] (1) Nonspecific adsorption detection of carboxyl magnetic beads
[0164] The products obtained in Comparative Examples 1 and 3 and Examples 10, 11 and 12 were subjected to nonspecific adsorption detection. The nonspecific adsorption of the magnetic microspheres was detected by fluorescently labeled bovine serum albumin. Specifically: take 2 mg of the product, add 3 ml of 20 mM sodium dihydrogen phosphate-disodium hydrogen phosphate, 0.5 M sodium chloride solution, pH: 7.8, mix thoroughly, magnetically separate and discard the supernatant, and repeat twice; resuspend the magnetic beads in 0.75 ml of 20 mM sodium dihydrogen phosphate-disodium hydrogen phosphate, 0.5 M sodium chloride solution, pH: 7.8, add 0.25 ml of 20 mM sodium dihydrogen phosphate-disodium hydrogen phosphate, 0.5 M sodium chloride solution, pH: 7.8 dissolved 1 mg / ml fluorescently labeled BSA (FITC-BSA), blow evenly, and put it in a shaker (220 rpm, 30°C) for 30 min; magnetically separate and take the supernatant, use Qubit 4 fluorimeter (Thermofisher, excitation 430-495 nm, detection 510-580 nm) to determine the amount of fluorescently labeled BSA remaining in the supernatant, and calculate the amount of fluorescently labeled BSA adsorbed per mg of magnetic beads (μg / mg) through the standard curve.
[0165] The specific results are shown in the table below:
[0166] Table 4 FITC-BSA concentration in supernatant and nonspecific adsorption results
[0167] Comparative Example 1 Comparative Example 3 Example 10 Embodiment 11 Example 12 FITC-BSA concentration in supernatant (μg / mL) 247.8 95.4 248.0 249.0 248.8 Nonspecific adsorption on carboxyl magnetic beads (μg / mg) 1.1 77.3 1.0 0.5 0.6
[0168] (2) Coupling efficiency detection
[0169] The coupling efficiency of the products obtained in Comparative Examples 1, 3 and Examples 10, 11 and 12 was tested. The coupling efficiency of the magnetic microspheres was tested by fluorescently labeled bovine serum albumin. Specifically, 50 mg of the products prepared in Comparative Examples 1, 3 and Examples 10, 11, and 12 were taken respectively, and 3 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6 was added, and the supernatant was discarded by magnetic separation, and the mixture was repeated twice; 0.75 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6 was used to resuspend the magnetic beads, 0.25 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6 dissolved 100 mg / ml 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), 50 mg / ml N-hydroxysuccinimide (NHS) were added, and after being blown evenly, the mixture was placed on a shaker (220 rpm, 30° C.) and shaken for 30 min; the supernatant was discarded by magnetic separation, 3 ml of 20 mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6 was used to resuspend the magnetic beads, and the supernatant was discarded by magnetic separation again, and 1 ml 20mM 4-morpholineethanesulfonic acid-sodium hydroxide solution, pH: 5.6, resuspend the magnetic beads for use; add 0.1ml fluorescently labeled bovine serum albumin (FITC-BSA) (15mg / ml) to 1.9ml, mix thoroughly, mix the magnetic beads in the previous step and add them to the diluted FITC-BSA, put them on a shaker (220rpm, 30℃) and shake for 2h; magnetically separate and take the supernatant, use Qubit 4 fluorometer (Thermofisher, excitation 430-495nm, detection 510-580nm) to determine the amount of fluorescently labeled BSA remaining in the supernatant, and calculate the coupling efficiency (%) through the standard curve. The results are shown in the following table:
[0170] Table 5 FITC-BSA concentration in the supernatant and coupling efficiency results
[0171] Comparative Example 1 Comparative Example 3 Example 10 Embodiment 11 Example 12 FITC-BSA concentration in supernatant (μg / mL) 29.0 163.5 17.5 14.0 18.5 Coupling efficiency (%) 94.2 67.3 96.5 97.2 96.3
[0172] It can be seen from Tables 4 and 5 that the comb-shaped polyurethane-coated magnetic microspheres of the present invention can improve protein coupling efficiency and reduce nonspecific adsorption compared with the method of introducing carboxyl groups on the linear polyurethane main chain in patent CN108192007A.
[0173] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing comb-shaped polyurethane-wrapped magnetic microspheres, characterized in that: The steps include: S1: mixing and reacting magnetic microspheres, diisocyanate monomers, and diol monomers including unsaturated diol monomers to obtain unsaturated linear polyurethane-coated magnetic microspheres; S2: reacting the unsaturated bonds on the unsaturated linear polyurethane to generate side chains, thereby obtaining the magnetic microspheres wrapped by the comb-shaped polyurethane; The reaction for generating the side chain is a polymerization reaction between the polymerizing agent and the unsaturated bonds on the unsaturated linear polyurethane; Alternatively, the reaction for generating the side chain is a coupling reaction between a coupling agent and an unsaturated bond on an unsaturated linear polyurethane.
2. The preparation method according to claim 1, characterized in that: In step S1, the magnetic microspheres and diisocyanate monomers are first mixed and reacted, and then the diol monomers are added and reacted.
3. The preparation method according to claim 2, characterized in that: In step S1, the reaction after adding the diol monomer includes a first reaction and a second reaction; The temperature of the first reaction is 40-120° C., the reaction time is 4-24 hours, and the molar ratio of the sum of the added diol monomer substances to the diisocyanate monomer is (0.1-0.5):1; The temperature of the second reaction is 80-120° C., the reaction time is 1-8 hours, and the molar ratio of the sum of the added diol monomer substances to the diisocyanate monomer is (1-6):
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that In the diol monomer, the molar ratio of the saturated diol monomer to the unsaturated diol monomer is (0-10 9 ):1, the preferred molar ratio is (0-10 6 ):1, the more preferred molar ratio is (0-10 3 ):1; The molecular weights of the unsaturated diol monomer, the saturated diol monomer and the diisocyanate monomer are all less than 2000 Da, preferably less than 1000 Da, and more preferably 100-600 Da.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, When the reaction for generating the side chain is a polymerization reaction, the specific reaction is to react the polymerizer with an initiator and magnetic microspheres coated with unsaturated linear polyurethane at 20-90° C. for 2-24 hours, wherein the mass ratio of the magnetic microspheres coated with unsaturated linear polyurethane to the polymerizer is 1:(0.2-10), and the mass ratio of the polymerizer to the initiator is 1:(0:001-0.1); When the reaction for generating side chains is a coupling reaction, the specific reaction is to react the coupling agent with the initiator unsaturated linear polyurethane coated magnetic microspheres at 20-80° C. for 2-24 hours, and the mass ratio of the unsaturated linear polyurethane coated magnetic microspheres to the coupling agent is 1:(0.001-10); the mass ratio of the coupling agent to the initiator is 1:(0:001-0.1).
6. The preparation method according to claim 5, characterized in that: In step S2, when the reaction for generating the side chain is a polymerization reaction, the specific reaction is to react the polymerizer with the initiator and the magnetic microspheres coated with unsaturated linear polyurethane at 40-80° C. for 4-16 hours, the mass ratio of the magnetic microspheres coated with unsaturated linear polyurethane to the polymerizer is 1:(0.5-5), and the mass ratio of the polymerizer to the initiator is 1:(0:005-0.05); When the reaction for generating side chains is a coupling reaction, the specific reaction is to react the coupling agent with the initiator unsaturated linear polyurethane coated magnetic microspheres at 40-70° C. for 4-16 hours, and the mass ratio of the unsaturated linear polyurethane coated magnetic microspheres to the coupling agent is 1:(0.001-0.1); the mass ratio of the coupling agent to the initiator is 1:(0:005-0.05).
7. The preparation method according to claim 6, characterized in that: The diisocyanate monomer is a compound having two isocyanate groups, including at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate; preferably at least one of toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate; The unsaturated diol monomer refers to a diol having an unsaturated bond, preferably a diol having a double bond, including at least one of 2,4-hexadiene-1,6-diol, 2-pentene-1,5-diol, 1,4-butene diol, 2,3-dihydroxy-1-butene, 3-allyloxy-1,2-propylene glycol, and 2-vinyl propane-1,3-diol; most preferably at least one of 1,4-butene diol, 2,3-dihydroxy-1-butene, 2-vinyl propane-1,3-diol, and 3-allyloxy-1,2-propylene glycol; The saturated diol monomer is a diol with a molecular weight less than 600Da, including at least one of diethanol, diethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol; The polymerizing agent includes at least one of vinyl monomers, acrylic monomers, acrylate monomers, and acrylamide monomers; The coupling agent comprises at least one of functionalized polyether, polyethylene glycol, polysaccharide, polypeptide, protein, nucleic acid or oligonucleic acid, preferably at least one of polyether, polyethylene glycol, polysaccharide, polypeptide, protein, nucleic acid or oligonucleic acid comprising thiol; The initiator includes at least one of an organic peroxide compound, a persulfate and an azo initiator.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The magnetic microspheres are porous, surface functionalized, and contain superparamagnetic crystals, and are prepared by any one of coprecipitation, oxidation precipitation, reduction precipitation, polymerization, or physical adsorption. The average particle size of the magnetic microspheres is 0.2-20 μm. The surface functionalized groups are at least one of hydroxyl, phenolic hydroxyl, ester, primary amine, secondary amine, urea, or amide groups, and the content of the groups is 10 -3 -10mmol / g; the iron element in the superparamagnetic crystal accounts for 10-60wt% of the total mass of the magnetic microspheres in terms of mass percentage; the specific surface area of the magnetic microspheres is 0.5-50m 2 / g, pore size is 5-50nm, porosity is 20-80%; Preferably, the magnetic microspheres are prepared by any one of coprecipitation, oxidation precipitation or reduction precipitation; the average particle size of the magnetic microspheres is 0.5-10 μm; the surface functionalized groups are at least one of hydroxyl groups or amino groups, and the group content is 0.05-5 mmol / g; the iron element in the superparamagnetic crystal accounts for 20-50% of the total mass of the magnetic microspheres in terms of mass percentage; the specific surface area of the magnetic microspheres is 3-30 m 2 / g, pore diameter is 10-30nm, and porosity is 20-60%.
9. The preparation method according to any one of claims 1 to 8, characterized in that: Before the reaction of step S1, the step of magnetically replacing the magnetic microspheres is also included. After the reaction of step S1, the step of washing and magnetically separating is also included. Before the reaction of step S2, the step of magnetically replacing the magnetic microspheres coated with unsaturated linear polyurethane is also included. After the reaction of step S2, the step of washing and magnetically separating is also included.
10. A comb-shaped polyurethane-wrapped magnetic microsphere, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carboxyl functionalized polyurethane coated magnetic microsphere and preparation method thereof
CN108192007A
Process for preparing coated magnetic particles
CN1849512A
Magnetic particles for diagnostic drug
JP2007127426A
Magnetic polymer particles and process for the preparation thereof
US4654267A